2020
DOI: 10.3390/nu13010136
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Women Diagnosed with Breast Cancer after a 12-Month Treatment of Lifestyle Modifications

Abstract: Healthy lifestyles are associated with better health-related quality of life (HRQoL), favorable prognosis and lower mortality in breast cancer (BC) survivors. We investigated changes in HRQoL after a 12-month lifestyle modification program in 227 BC survivors participating in DEDiCa trial (Mediterranean diet, exercise, vitamin D). HRQoL was evaluated through validated questionnaires: EQ-5D-3L, EORTC-QLQ-C30 and EORTC QLQ-BR23. Baseline changes were tested using analysis of variance. Multiple regression analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 48 publications
1
34
0
Order By: Relevance
“…It is well confirmed that cancer patients report declined functional capacity, increased pain and generally reduced quality of life, which may deteriorate treatment efficacy and lead to poor disease prognosis [ 57 ]. Dietary and lifestyle modification have been reported to ameliorate quality of life aspects in BC patients [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well confirmed that cancer patients report declined functional capacity, increased pain and generally reduced quality of life, which may deteriorate treatment efficacy and lead to poor disease prognosis [ 57 ]. Dietary and lifestyle modification have been reported to ameliorate quality of life aspects in BC patients [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is well confirmed that cancer patients report declined functional capacity, increased pain and generally reduced quality of life, which may deteriorate treatment efficacy and lead to poor disease prognosis [ 57 ]. Dietary and lifestyle modification have been reported to ameliorate quality of life aspects in BC patients [ 57 ]. Likewise in our study, patients following MD for 3 months reported significant improvements in global health/quality of life, role functioning, emotional functioning, depression and anxiety, as well as trends of improvement in cognitive functioning, pain, insomnia, constipation and systemic therapy side effects.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, several studies have demonstrated that nutrition represents an important protective factor against the development of tumors ( 150 ) but also represents an effective therapeutic intervention for patients with cancer ( 151 , 152 ). In this context, several studies have demonstrated that dietary and lifestyle interventions during cancer treatments can ameliorate the adherence to treatment as well as patient quality of life and prognosis [hazard ratio (HR) for physical activity, 0.60; 95% CI, 0.39-0.92; P=0.02; HR for highest vs. lowest tertile of quality diet, 0.73; 95% CI, 0.55 to 0.97; P=0.03] ( 153 - 156 ). These data, together with the clinical features of patients allow clinicians to determine the best therapeutic approach as well as to predict the prognosis and outcomes of patients ( 157 ).…”
Section: Ovarian Cancer Management: From Linear To Multidisciplinary Patient-centered Care Approachmentioning
confidence: 99%
“…The occupational physician can also implement health promotion programs targeting the primary individual risk factors, promoting healthy lifestyle behaviours, for example supporting the introduction of a Mediterranean diet, that has been shown to be associated with a lower risk of BC incidence in women ( 94 , 95 ). The typical Mediterranean diet nutrients have shown a positive influence on the expression of inflammatory biomarkers, oxidative stress, DNA damage and genetic modifications, all aspects that can affect BC outcomes ( 96 , 97 ).…”
Section: Risk Assessment and Prevention Strategiesmentioning
confidence: 99%
“…The typical Mediterranean diet nutrients have shown a positive influence on the expression of inflammatory biomarkers, oxidative stress, DNA damage and genetic modifications, all aspects that can affect BC outcomes ( 96 , 97 ). Moreover, lifestyle modifications can positively impact BC survival, whose lower health-related quality of life negatively affects treatment compliance and disease outcomes ( 98 ).…”
Section: Risk Assessment and Prevention Strategiesmentioning
confidence: 99%